Luther H. Martin and Donald Wiebe, eds, Religion Explained? The Cognitive Science of Religion after Twenty-Five Years. (21st September 2018) - Larson, Jennifer
Abstract : Luther H. Martin and Donald Wiebe, eds, Religion Explained? The Cognitive Science of Religion after Twenty-Five Years (London and New York: Bloomsbury, 2017), xi + 260 pp. $102.60 (hbk). ISBN: 978-1-35003-246- 0; $39.95 (pbk). ISBN: 978-1-35010-592-8; $102.60 (PDF eBook). ISBN: 978-1-35003-247-7.